Electrochemical synthesis of nickel-aluminium oxide system from metals obtained by ore processing; IOP Conference Series: Earth and Environmental Science; Vol. 27 : Problems of Geology and Subsurface Development - Korobochkin V. V. Valery Vasilievich; Usoltseva N. V. Natalia Vasilievna; Shorokhov K. G.; Popova E. V. (Integrated Use and Processing of Mineral Resources, 2015)
Title screen